Can root-associated fungi mediate the impact of abiotic conditions on the growth of a High Arctic herb? - Wutkowska, Magdalena; Ehrich, Dorothee; Mundra, Sunil; Vader, Anna; Eidesen, Pernille Bronken (Soil Biology and Biochemistry, 2021)
Arctic plants are affected by many stressors. Root-associated fungi are thought to influence plant performance in stressful environmental conditions. However, the relationships are not well-known; do the number of fungal partners, their ecological functions and community composition mediate the impact of environmental conditions and/or influence host plant performance? To address these questions, we used a common arctic plant as a model system: Bistorta vivipara . Whole plants (including root system, n = 214) were collected from nine locations in Spitsbergen. Morphometric features were measured as a proxy for plant performance and combined with metabarcoding datasets of their root-associated fungi (amplicon sequence variants, ASVs), edaphic and meteorological variables. Seven biological hypotheses regarding fungal influence on plant measures were tested using structural equation modelling. The best-fitting model revealed that local temperature affected plants both directly (negatively aboveground and positively below-ground) and indirectly - mediated by fungal richness and the ratio of symbio- and saprotrophic ASVs. The influence of temperature on host plants is therefore complex and should be examined further. Fungal community composition did not impact plant measurements and plant reproductive investment was not influenced by any fungal parameters. The lack of impact of fungal community composition on plant performance suggests that the functional importance of fungi is more essential for the plant than their identity.